Implementation Of Geogebra As A Mathematics Learning Medium By Applying A Problem-Based Learning Model (Pbm) - Panjaitan, Melda (Cattleya Darmaya Fortuna, 2024)
Evaluate the impact of using GeoGebra as learning media on students' understanding of mathematical concepts and their engagement in the learning process. The method used in this study was experimental research with a pre-test and post-test design, where students were given problem-based tasks that were solved using GeoGebra. Data were collected through pre-test and post-test to assess the improvement of students' understanding of mathematical concepts, as well as observation to evaluate students' engagement during the learning process. The results showed that the use of GeoGebra in the Problem-Based Learning (PBL) model significantly improved students' understanding of mathematical concepts, with an average increase in understanding scores of 25%. The findings support the integration of GeoGebra with the PBL model as an effective strategy in learning mathematics in secondary schools.